The aging process and challenges for the job market in Brazil - Pessôa, Elisângela Maia; Gouvêa, Paula Machado; Mattos, Bruna Silva de; Almeida, Andreia Cristina da Silva (Argumentum, 2025)
This article sets out the insertion rates of elderly people within the Brazilian job market to highlight the challenges of aging in capitalist society. It is based on mixed documentary research, focused on indexes provided by the Brazilian Institute of Geography and Statistics, the Institute of Applied Economic Research, the Annual Social Information List, and the National Employment System, supported by a bibliographic survey. There is an evident age bias towards the inclusion of elderly people in the job market. The elderly population is not the most likely to experience unemployment and joblessness, it is in second place in terms of access after young people. Research bodies indicate that since 2016 the number of unemployed elderly people has been increasing, and that, faced with this scenario, they have been entering the informal job market.
Keywords: Aging; Elderly; Job market